Agenciamento algorítmico na experiência de consumo online - Carvalho, Fernanda Lagroteria Ribeiro de (Universidade do Vale do Rio dos Sinos, 2023)
All experiences nowadays are permeated by mediatization, from the simplest to the most complex, they are imbued by our relationship with technology. We are users when we browse these technicalities for leisure or work, and when we need to purchase products. There, our trails are data, which when interpreted by the platforms, allow advertisers to direct our navigation according to algorithmic logics, which are determined by commercial logics. In this context, this study observes the crossings that occur during the browsing experience, seeking to metaphorize the paths that users take and how the algorithms manage these crossings that converge to the act of buying. The purpose here is to understand these dynamics and bring to light the processes that occur during the experience. for this, we use mediatization studies to unravel the particularities of the new digital ambiences. The methodology adopted included bibliographical research with critical analysis of the author's perspectives, interviews with consumers, and online autoethnography to collect empirical data, an exercise in which we simulated the purchase intention of a smartphone on Google and online retail store Magazine Luiza. It was possible to identify, among other things, that the user who browses identified and with tracking and cookies permission, receives 66% more crossings than the one who browses without such permissions. We also noticed an 88.8% preference for Google while product searching, in addition to the platform's protagonism, demonstrating that recommendation system algorithms are intelligent agents in dispute. Finally, we note that users seek to exercise counterforces in relation to the directions received, using subterfuges to avoid them, which can demonstrate distrust in relation to the tracking mechanism and the companies involved.
Keywords: Algoritmos; Agenciamento; Consumo online; Midiatização; Algorithms; Agencying; Online consumption; Mediatization; ACCNPQ::Ciências Sociais Aplicadas::Comunicação